Analysis Of Language Errors Committed By Students In Indonesian Language Learning: A Qualitative Study Of Secondary School Students - Riza Rahmadani Piliang; Frisdayanti Tambunan; Nurul Anisyah Siregar; Dini Safitri; Lannuri Hasibuan; Alfarizi Satria Lubis; Nurdalilah Nurdalilah (International Journal of Community Service (IJCS), 2026)
Language competence is essential for students’ academic achievement and effective communication. This study aims to identify and analyze language errors in Indonesian language learning and determine the factors contributing to these errors. A qualitative descriptive approach was employed involving 50 students, 3 teachers, 2 school administrators, and 10 parents. Data were collected through observations, interviews, focus group discussions, learning journals, document analysis, and field notes, and analyzed using thematic analysis. The findings revealed five categories of language errors: spelling, diction, morphology, syntax, and ineffective sentence construction. Syntactic errors were the most dominant (35%), followed by spelling errors. Contributing factors included local language interference, limited mastery of grammar, low reading habits, insufficient exposure to academic texts, and the influence of social media language. The study also found that literacy-based instruction, intensive writing practice, collaborative learning, and continuous teacher feedback effectively reduced language errors and improved language proficiency. These findings provide valuable implications for developing more effective Indonesian language teaching strategies and strengthening students’ academic literacy skills.